2012
DOI: 10.1148/radiol.12111942
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Lesion Assessment: Comparison of Whole-Body Hybrid MR/PET and PET/CT Imaging—Pilot Study

Abstract: MR/PET imaging of the lung is feasible and provides diagnostic image quality in the assessment of pulmonary masses. Similar lesion characterization and tumor stage were found in comparing PET/CT and MR/PET images in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
92
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 36 publications
1
92
0
4
Order By: Relevance
“…Wholebody integrated PET/MRI scanners provide diagnostic image quality and comparably good lesion characterization and tumor staging in pulmonary masses as compared with PET/CT [16]. In this study we were able to demonstrate a significant inverse correlation of the SUV and ADC values assessed with simultaneous PET/MRI examination.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Wholebody integrated PET/MRI scanners provide diagnostic image quality and comparably good lesion characterization and tumor staging in pulmonary masses as compared with PET/CT [16]. In this study we were able to demonstrate a significant inverse correlation of the SUV and ADC values assessed with simultaneous PET/MRI examination.…”
mentioning
confidence: 50%
“…Already published clinical studies using whole-body PET/MRI in oncologic patients confirmed its feasibility for whole-body cancer staging and reported an image quality comparable to that of PET/CT for lesion detection [15 -17]. In a pilot study with 10 patients, Schwenzer et al recently highlighted the potential of PET/MR for the assessment of pulmonary masses, showing a similar lesion characterization and tumor stage compared to PET/CT [16]. Regier and colleagues demonstrated a significant inverse correlation between the SUVmax determined by FDG-PET/CT and the ADC in NSCLC [18].…”
mentioning
confidence: 94%
“…bronchial carcinoma) showed that PET/MRI had as good potential as PET/CT to characterize tumor lesion (i.e. pulmonary masses) and tumor stage with quality [55].…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…For instance, detection of pulmonary lesions is still limited in MRI compared to CT. Although MRI seems to be sufficient for pulmonary staging on a patient basis [45], small lung lesions can be missed in MRI [46]. It is thus recommended to perform an additional lung CT in patients with clinically relevant risk for pulmonary spread, e. g., in the initial staging of sarcoma.…”
mentioning
confidence: 99%
“…Typically, PET/MRI studies are performed in order to assess the diagnostic value of PET/MRI compared to other modalities for specific patient populations and clinical questions. Often, PET/ MRI is directly compared to PET/CT in these studies [7,8,10,21,38,45,47]. Performing studies of this kind in children is highly challenging.…”
mentioning
confidence: 99%